Magnetic fibrous sorbent for remote and efficient oil adsorption. Issue 1 (15th July 2017) - Song, Botao; Zhu, Jie; Fan, Haiming
Abstract: Oil spill accident and oily water have potential risks to environment and human health, thus need to be imperatively treated. Herein, a magnetic fibrous sorbent was designed via electrospinning of suspension containing polymer and magnetic nanoparticles in one step for remote and efficient oil adsorption. The morphology of the magnetic fibrous sorbent was characterized by scanning electron microscopy. The magnetic property and the wetting behavior were measured by vibrating sample magnetometer and contact angle system, respectively. The results showed that the morphology of the fibers was homogeneous and the magnetic nanoparticles were well dispersed within the fibers. It was also found that this composite sorbent had good magnetic response, special wettability, and remote oil adsorption capacity. We believed this novel polymer/Fe3 O4 fibrous sorbent could be used as a promising material for the remote oil/water separation. Graphical abstract: Highlights: A magnetic fibrous sorbent was designed by electrospinning. The sorbent had good magnetic response and special wettability. The magnetic fibrous sorbent showed good remote oil adsorption capacity.